Comparing the Absorbed dose of Lung and Conformity and Heterogeneity Indexes of Breast Tumor for Mastectomy Patients Using Photon and Electron Beams - Davod Borji; Nooshin Banaee Rezaeeyeh; Hassan Ali Nedaie (Fasa University of Medical Sciences, 2020)
Background & objective: The aim of this study is to evaluate the feasibility of using electron therapy as main treatment modality of mastectomy patients and determine the absorbed dose of lung and heterogeneity and conformity indexes of breast region in this technique and compare it with the conventional method of applying tangential photon beams. Materials & methods: In this study, the CT images of 10 mastectomy patients were used. The CT images were imported into Monaco treatment planning system. Targets and organs at risk were contoured by a radiation oncologist. Then, for each patient, two treatment plans were designed: one with photon fields and the other with electron fields. The prescription dose for each plan was 50 Gy and the plans were designed in a way to deliver 90% of prescription to at least 90% of target volume. Conformity and heterogeneity indexes and absorbed dose of lung were then evaluated and compared. Results: Comparing the obtained data, it was shown that photon fields provided better conformity and heterogeneity compared to electron fields. Also, due to the different irradiation angles of photon and electron fields, in most patients, photon fields led to lower absorbed dose of lung. Conclusion: The results of this study showed that in terms of sparing lung and delivering a homogeneous and conformal dose to tumor, radiotherapy of mastectomy cases with tangential photon fields have better results compared to electron therapy.